Стабілізація маятниками положення осі обертання ізольованого абсоабсолютно твердого тіла - Філімоніхін, Г. Б. (ВПЦ "Київський університет", 2002)
Розглянуто задача стабілізації маятниками положення осі обертання ізольованого абсолютно твердого тіла відносно самого тіла. Ізольоване тіло рухається плоскопаралельно. На його вісь обертання насаджено два однакових математичних маятника. Усередині тіла знаходиться маса, що може переміщуватися. Знайдено необхідні і достатні умови асимптотичної стійкості основного руху системи – рух, у якому маятники компенсують внутрішнє переміщення мас у системі й система обертається навколо осі обертання тіла. Is considered the problem of stabilization, by the pendulums, of the position of the axis of the rotation of the isolated absolute rigid body concerning itself. The isolated absolute rigid body makes plane-parallel motions. On the central axis of the absolute rigid body, which is perpendicular to the plane of motion is installed two identical mathematical pendulums. Inside the absolute rigid body there is a material point, which can move. Is established, that, under condition of existence, the main motion of a system – the motion, in which the pendulums compensate the unbalance of material point and the system rotates around the central axis of the absolute rigid body, is asymptotically stable.
Stabilizations by pendulums of the position of the axes of the rotation of the isolated absolute rigid body
Keywords: абсолютно тверде тіло; стабілізація; математичні маятники; асимптотична стійкість; основний рух